Challenges to Physicians: Hospital Immunity and Sham Peer Review - Robert Poston; Farid Gharagozloo; Rainer W.G. Gruessner (Journal of Human Psychology, 2023)
An opinion essay examines hospital immunity doctrines and alleged sham peer review, outlining legal context, patient‑safety implications, and avenues for due process.
Keywords: Hospital Immunity